2018
DOI: 10.1002/jclp.22673
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in mentalization predict improvements in interpersonal distress in patients with mental disorders

Abstract: ObjectivesAssociations between interpersonal problems and mentalization have rarely been investigated. In this study, we explored patterns of interpersonal problems, mentalization, symptom severity, and attachment during inpatient treatment and at follow‐up. Additionally, we investigated whether mentalization predicts a decrease in interpersonal distress.Method We analyzed time‐series data from patients with mental disorders. Data were collected at the beginning and at the end of inpatient treatment, and appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 44 publications
(64 reference statements)
3
22
0
2
Order By: Relevance
“…For example, Herpertz and Bertsch (2014) considered impairments in social cognition (i.e., facial emotion recognition, cognitive and emotional empathy, and theory of mind) to be a core concept that characterizes PDs. Other authors (Antonsen et al, 2016; Hayden et al, 2018) found an association between Reflective Function (RF) and the intensity of symptom distress and psychosocial impairment. Semerari et al (2014) supported evidence that (1) metacognition is specifically impaired in PDs if compared to a clinical sample of non-PD patients, (2) the dysfunction is significantly correlated to the severity of personality pathology (measured as the number of criteria met in the SCID II) and (3) difficulties in metacognition are specific to different PDs (Semerari et al, 2007), for example in BPD (Semerari et al, 2005, 2015) and in Avoidant PD (AvPD) patients Pellecchia et al (2018).…”
Section: Discussionmentioning
confidence: 98%
“…For example, Herpertz and Bertsch (2014) considered impairments in social cognition (i.e., facial emotion recognition, cognitive and emotional empathy, and theory of mind) to be a core concept that characterizes PDs. Other authors (Antonsen et al, 2016; Hayden et al, 2018) found an association between Reflective Function (RF) and the intensity of symptom distress and psychosocial impairment. Semerari et al (2014) supported evidence that (1) metacognition is specifically impaired in PDs if compared to a clinical sample of non-PD patients, (2) the dysfunction is significantly correlated to the severity of personality pathology (measured as the number of criteria met in the SCID II) and (3) difficulties in metacognition are specific to different PDs (Semerari et al, 2007), for example in BPD (Semerari et al, 2005, 2015) and in Avoidant PD (AvPD) patients Pellecchia et al (2018).…”
Section: Discussionmentioning
confidence: 98%
“…However, we also took into consideration that the severity of psychiatric symptoms can have a serious impact on inner psychic processes [29, 30]. Previous studies have demonstrated that this may affect research regarding the aforementioned concepts as well [27, 31, 32]. Therefore, we also included this variable in our research.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, affect regulation – an important component of mentalization – turned out to mediate the association between attachment insecurities and interpersonal problems [17]. Furthermore, one study reported stable patterns of intercorrelation between measures of adult attachment, interpersonal problems, and mentalization over the course of inpatient psychotherapy [27], and one study revealed specific patterns of attachment-deactivating and -hyperactivating strategies, an impairment in reflective functioning, and an increase in interpersonal problems [28]. …”
Section: Introductionmentioning
confidence: 99%
“…Mentalization is positively intercorrelated with mental stability and attachment security. A growing number of studies have emphasized the importance of mentalization as a protective factor against mental disorders (10)(11)(12). On the other hand, impairments in the ability to mentalize are predictors of psychopathology and mental instability (3,8).…”
Section: Introductionmentioning
confidence: 99%
“…Both disorders are characterized by a lack of mentalization, and both disorders are characterized by the predominance of immature defense mechanisms ( 34 , 35 ). Furthermore, both the enhancement of reflective functioning and the maturation of defense mechanisms are associated with mental stability and with progress in psychotherapy, e.g., in the treatment of personality disorders ( 11 , 28 , 36 , 37 ). Since mentalization enables humans to reflect upon their own actions and, in particular, to reflect upon the mental processes that cause their own actions, an association of mentalization with the use of various kinds of defense mechanisms seems plausible.…”
Section: Introductionmentioning
confidence: 99%